2019
DOI: 10.1039/c9dt00613c
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical porous MnCo2O4 yolk–shell microspheres from MOFs as secondary nanomaterials for high power lithium ion batteries

Abstract: Hierarchical porous MnCo2O4 yolk–shell microspheres have been synthesized via a facile chemical precipitation method with subsequent calcination treatment, showing high reversible lithium storage capacity, excellent cyclic performance and enhanced rate capability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 51 publications
1
29
0
Order By: Relevance
“…The XPS spectrum of Co 2p can be fitted by considering two spin–orbit doublet characteristics of Co 3+ and Co 2+ , indicating the existence of Co with different valence states (Co 3+ and Co 2+ ) (Figure 3b). 40 The two peaks located at 780.2 (Co 2p 3/2 ) and 795.6 eV (Co 2p 1/2 ) could be ascribed to Co 3+ , while the peaks located at 780.9 (Co 2p 3/2 ) and 795.5 eV (Co 2p 1/2 ) could be ascribed to Co 2+ . Similarly, as exhibited in Figure 3c, the spectrum of Mn 2p also indicates the presence of Mn 2+ and Mn 3+ .…”
Section: Resultsmentioning
confidence: 93%
“…The XPS spectrum of Co 2p can be fitted by considering two spin–orbit doublet characteristics of Co 3+ and Co 2+ , indicating the existence of Co with different valence states (Co 3+ and Co 2+ ) (Figure 3b). 40 The two peaks located at 780.2 (Co 2p 3/2 ) and 795.6 eV (Co 2p 1/2 ) could be ascribed to Co 3+ , while the peaks located at 780.9 (Co 2p 3/2 ) and 795.5 eV (Co 2p 1/2 ) could be ascribed to Co 2+ . Similarly, as exhibited in Figure 3c, the spectrum of Mn 2p also indicates the presence of Mn 2+ and Mn 3+ .…”
Section: Resultsmentioning
confidence: 93%
“…It is not difficult to see that there is a semicircle in the high frequency region and the intermediate frequency region, which is due to the formation of an SEI after cycling. 55 The first semicircle in the high frequency region is represented by R e in the equivalent circuit, while the second semicircle in the intermediate frequency region is represented by R ct . The equivalent circuit model was composed of R e , SEI resistance ( R s ), R ct , Warburg impedance ( W 1 ), and constant phase element.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It can be found that the specific capacity of the SCG-1100 hybrid decays first in the first 30th cycle and then rises in the following cycles, which is very similar to previous reports. 4 , 6 The first decay is due to the volume expansion effect of silicon particles in the cycling process. The repetitive volume changes could fracture the SEI layers and result in a more extensive exposure of Si active sites during the lithiation process.…”
Section: Results and Discussionmentioning
confidence: 99%